Diabetes is associated with risk of postoperative cognitive dysfunction: A meta‐analysis. Issue 5 (23rd February 2017) - Feinkohl, I.; Winterer, G.; Pischon, T.
Abstract: Background: Postoperative cognitive dysfunction (POCD) occurs frequently after surgery, particularly among older people. Diabetes, chronic hyperglycemia, and a history of hypoglycemia are related to cognitive impairment, but little is known about their roles in POCD. Here, we estimated their associations with risk of POCD on the basis of published epidemiological research. Methods: The PubMed and Cochrane databases were searched for longitudinal studies of adults undergoing surgery with reporting of associations of diabetes status, glycemic levels, and/or a history of hypoglycemia with risk of POCD as relative risks or odds ratios. Meta‐analysis Of Observational Studies in Epidemiology (MOOSE) and Preferred Reporting Items for Systematic Reviews and Meta‐analyses (PRISMA) guidelines were followed. Results: The search identified 246 publications of which 14 met inclusion criteria, reporting on a total of 2642 patients (mean age 64 y). Follow‐up periods spanned 1 day to 5 years. Overall, patients with diabetes had a 1.26‐fold higher risk of POCD compared with diabetes‐free patients (95% CI, 1.12–1.42). A single study assessed glycemic control in patients with diabetes and identified a higher hemoglobin A1c (HbA1c) level as associated with higher POCD risk (relative risk per percent higher HbA1c, 2.0; 95% CI, 1.4–2.6). We did not find studies on glycemic levels in the nondiabetic range or on hypoglycemia as potential predictors of POCD. Conclusion: Patients with diabetes appear to have a higher risk of POCD compared with diabetes‐free persons. Among patients with diabetes, POCD risk may further increase with poorer glycemic control as indexed by higher HbA1c. The roles of HbA1c levels among nondiabetic persons in POCD risk warrant further research.